The construction of a grapheme-to-phone algorithm for Danish - Molbæk Hansen, Peter (Annual Report of the Institute of Phonetics University of Copenhagen, 1982)
The paper presents the main strategy and some preliminary results of the current work with the construction of a grapheme-to phone algorithm forming part of a text-to-speech algorithm for Danish. The paper also discusses the main difficulties connected with this work, and a brief report of the present status of the project is given.